UVIT view of ram-pressure stripping in action: star formation in the stripped gas of the GASP jellyfish galaxy JO201 in Abell 85. Issue 3 (2nd June 2018) - George, K; Poggianti, B M; Gullieuszik, M; Fasano, G; Bellhouse, C; Postma, J; Moretti, A; Jaffé, Y; Vulcani, B; Bettoni, D; Fritz, J; Côté, P; et al.
ABSTRACT: Jellyfish are cluster galaxies that experience strong ram-pressure effects that strip their gas. Their Hα images reveal ionized gas tails up to 100 kpc, which could be hosting ongoing star formation. Here, we report the ultraviolet (UV) imaging observation of the jellyfish galaxy JO201 obtained at a spatial resolution ∼1.3 kpc. The intense burst of star formation happening in the tentacles is the focus of this study. JO201 is the 'UV-brightest cluster galaxy' in Abell 85 ( z ∼ 0.056) with knots and streams of star formation in the UV. We identify star-forming knots both in the stripped gas and in the galaxy disc and compare the UV features with the ones traced by Hα emission. Overall, the two emissions remarkably correlate, both in the main body and along the tentacles. Similarly, also the star formation rates of individual knots derived from the extinction-corrected far-ultraviolet (FUV) emission agree with those derived from the Hα emission and range from ∼0.01 to 2.07 M⊙  yr −1 . The integrated star formation rate from FUV flux is ∼15 M⊙  yr −1 . The unprecedented deep UV imaging study of the jellyfish galaxy JO201 shows clear signs of extraplanar star formation activity due to a recent/ongoing gas stripping event.